An enhancement of fault-tolerant routing protocol for Wireless Sensor Network - Zamree, Che-Aron; Mohammed Al-Khateeb, Wajdi Fawzi; Anwar, Farhat (2010)
As more and more real Wireless Sensor Network's (WSN) applications have been tested and deployed over the last decade, the research community of WSN realizes that several issues need to be revisited from practical angles, such as reliability and availability. Furthermore, fault-tolerance is one of the main issues in WSNs since it becomes critical in real deployed environments where network stability and reduced inaccessibility times are important. Basically, wireless sensor networks suffer from resource limitations, high failure rates and faults caused by the defective nature of wireless communication and the wireless sensor itself. This can lead to situations, where nodes are often interrupted during data transmission and blind spots occur in the network by isolating some of the devices. In this paper, we address the reliability issue by designing an enhanced faulttolerant mechanism for Ad hoc On-Demand Distance Vector (AODV) routing protocol applied in WSN called the ENhanced FAult-Tolerant AODV (ENFAT-AODV) routing protocol. We apply a backup route technique by creating a backup path for every node on a main path of data transmission. When a node gets failure to deliver a data packet through the main path, it immediately utilizes its backup route to become a new main path for the next coming data packet delivery to reduce a number of data packets dropped and to maintain the continuity of data packet transmission in presence of some faults (node or link failures). Furthermore, with increased failure rate, this proposed routing protocol improves the throughput, reduces the average jitter, provides low control overhead and decreases the number of data packets dropped in the network. As a result, the reliability, availability and maintainability of the network are achieved. The simulation results show that our proposed routing protocol is better than the original AODV routing.